Unraveling cross-reactivity of anti-glycan IgG responses in filarial nematode infections - Petralia, Laudine M. C.; van Diepen, Angela; Nguyen, Dieu-Linh; Lokker, Lena A.; Sartono, Erliyani; Bennuru, Sasisekhar; Nutman, Thomas B.; Pfarr, Kenneth; Hoerauf, Achim; Wanji, Samuel; Foster, Jeremy M.; Hokke, Cornelis H. (Frontiers in Immunology, 2023)
Parasitic nematodes responsible for filarial diseases cause chronic disablement in humans worldwide. Elimination programs have substantially reduced the rate of infection in certain areas, but limitations of current diagnostics for population surveillance have been pointed out and improved assays are needed to reach the elimination targets. While serological tests detecting antibodies to parasite antigens are convenient tools, those currently available are compromised by the occurrence of antibodies cross-reactive between nematodes, as well as by the presence of residual antibodies in sera years after treatment and clearance of the infection. We recently characterized the N-linked and glycosphingolipid derived glycans of the parasitic nematode Brugia malayi and revealed the presence of various antigenic structures that triggered immunoglobulin G (IgG) responses in infected individuals. To address the specificity of IgG binding to these glycan antigens, we screened microarrays containing Brugia malayi glycans with plasma from uninfected individuals and from individuals infected with Loa loa, Onchocerca volvulus, Mansonella perstans and Wuchereria bancrofti, four closely related filarial nematodes. IgG to a restricted subset of cross-reactive glycans was observed in infection plasmas from all four species. In plasma from Onchocerca volvulus and Mansonella perstans infected individuals, IgG binding to many more glycans was additionally detected, resulting in total IgG responses similar to the ones of Brugia malayi infected individuals. For these infection groups, Brugia malayi, Onchocerca volvulus and Mansonella perstans, we further studied the different IgG subclasses to Brugia malayi glycans. In all three infections, IgG1 and IgG2 appeared to be the major subclasses involved in response to glycan antigens. Interestingly, in Brugia malayi infected individuals, we observed a marked reduction in particular in IgG2 to parasite glycans post-treatment with anthelminthic, suggesting a promising potential for diagnostic applications. Thus, we compared the IgG response to a broad repertoire of Brugia malayi glycans in individuals infected with various filarial nematodes. We identified broadly cross-reactive and more specific glycan targets, extending the currently scarce knowledge of filarial nematode glycosylation and host anti-glycan antibody response. We believe that our initial findings could be further exploited to develop disease-specific diagnostics as part of an integrated approach for filarial disease control.